Skin fibroblast functional heterogeneity in health and disease - Tjaša Bensa; Stavroula Tekkela; Emanuel Rognoni (2023)
Abstract Fibroblasts are the major cell population of connective tissue, including the skin dermis, and are best known for their function in depositing and remodelling the extracellular matrix. Besides their role in extracellular matrix homeostasis, fibroblasts have emerged as key players in many biological processes ranging from tissue immunity and wound healing to hair follicle development. Recent advances in single‐cell RNA‐sequencing technologies have revealed an astonishing transcriptional fibroblast heterogeneity in the skin and other organs. A key challenge in the field is to understand the functional relevance and significance of the identified new cell clusters in health and disease. Here, we discuss the functionally distinct fibroblast subtypes identified in skin homeostasis and repair and how they evolve in fibrotic disease conditions, in particular keloid scars and cancer. © 2023 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.